2009
DOI: 10.1007/s11192-009-0136-5
|View full text |Cite
|
Sign up to set email alerts
|

Comparing the early research performance of PhD graduates in labor economics in Europe and the USA

Abstract: This paper analyzes the early research performance of PhD graduates in labor economics, addressing the following questions: Are there major productivity differences between graduates from American and European institutions? If so, how relevant is the quality of the training received (i.e. ranking of institution and supervisor) and the research environment in the subsequent job placement institution? The population under study consists of labor economics PhD graduates who received their degree in the years 2000… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 22 publications
0
8
0
Order By: Relevance
“…However all major European countries (France, Germany, Netherlands, Spain) have experienced a growth of publications over time. For a similar trend, see Neary, Mirrlees, and Tirole (), Cardoso, Guimaraes, and Zimmermann (), Matthiessen, Schwarz, and Find (), and Hamermesh ().…”
mentioning
confidence: 65%
See 1 more Smart Citation
“…However all major European countries (France, Germany, Netherlands, Spain) have experienced a growth of publications over time. For a similar trend, see Neary, Mirrlees, and Tirole (), Cardoso, Guimaraes, and Zimmermann (), Matthiessen, Schwarz, and Find (), and Hamermesh ().…”
mentioning
confidence: 65%
“…In the last 40 years the EU has implemented several policies supporting research at the national and European level that have resulted in increasing output (Cardoso, Guimaraes, and Zimmermann ; Neary, Mirrlees, and Tirole ) and in a convergence toward the North American model of education and research (Borghans and Cörvers ). The launch of the framework programs for research (1984), the increased mobility of researchers fostered by the European Single Market (1992) and promoted by the European Research Area (2000) together with the policy elaborated according to the Lisbon strategy have made the European market for economists more homogeneous and more reactive to the worldwide increasing pressure to publish as a condition to get an academic job or a promotion (Frey 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Generally, the American PhD programmes featured a strong emphasis on mathematical modelling and econometric techniques. Cardoso et al. (2008) found that the quality of research by PhDs from US universities was better than the research of European PhDs.…”
Section: Economists From the Land Of The Long White Cloudmentioning
confidence: 99%
“…Generally, the American PhD programmes featured a strong emphasis on mathematical modelling and econometric techniques. Cardoso et al (2008) found that the quality of research by PhDs from US universities was better than the research of European PhDs. Doctoral programmes in British, Australian and New Zealand universities, in contrast, involve the submission of a thesis that amounts to a substantial (publishable) monograph.…”
Section: Economists From the Land Of The Long White Cloudmentioning
confidence: 99%
“…Research rankings have become a popular tool for the evaluation of research performance on both individual and institutional levels. Cardoso et al (2010) have used individual data analysis to compare trends in publication success among labor economists between Europe, the US, and other world regions. Rankings are increasingly used for funding allocation and are gaining increasing influence in tenure appointments.…”
Section: Introductionmentioning
confidence: 99%